Implementation of Good Faith Principles in Trademark Registration in Indonesia - Carina Budi Siswani (Dinasti Research, 2025)
In the era of globalization and free trade, trademarks play a strategic role as the identity, reputation, and quality assurance of products and services. Therefore, the trademark registration system must provide fair and effective legal protection. The principle of good faith is one of the fundamental pillars of Indonesia’s trademark registration system, as stipulated in Article 21 paragraph (3) of Law Number 20 of 2016 concerning Trademarks and Geographical Indications. This principle aims to prevent trademark registrations made in bad faith, such as copying or exploiting the reputation of existing trademarks. This study employs a normative legal research method with statutory, conceptual, and case approaches. The findings indicate that the application of the good faith principle is implemented through administrative and substantive examinations by the Directorate General of Intellectual Property (DJKI), third-party objection mechanisms, and judicial oversight. Cases such as Pierre Cardin, VANS, and Geprek Bensu illustrate the importance of this principle in upholding substantive justice and protecting legitimate trademark owners. However, its implementation faces several challenges, including difficulties in proving bad faith, limited institutional capacity, and low awareness among business actors. Therefore, strengthening technical regulations, enhancing institutional capacity, and utilizing information technology are strategic steps to optimize the implementation of the good faith principle in Indonesia’s trademark registration system.